Dual-Mode Large-Mode-Area Multicore Fiber With Air-Hole Structure - Mengxin Yang; Yudong Lian; Jingbo Wang; Yuqin Zhang (IEEE Photonics Journal)
A novel dual-mode large-mode-area multicore fiber with air-hole structure, which is a quasi-37 core structured fiber with 20 air holes and 17 cores, is proposed in this paper. This fiber can realize strict dual-mode operation, that is, the fundamental mode HE11 and the second-order mode HE21 operation. The air-hole structure makes the second-order modes TE01 and TM01 cut off. Effects of structural parameters on effective refractive index and effective area of fundamental mode are investigated systematically. By optimizing the structural parameters of the fiber, effective area of fundamental mode is up to 1557.91 μm2 and maintaining a low bending loss (less than 10−4 dB/m at R > 0.47 m) while keeping dual-mode operation. The fiber can be used for large-mode-area high-power optical fiber laser, amplifier, FTTH and so on.